Is it a sense of autonomy, control, or attachment? Exploring the effects of in-game customization on game enjoyment. (July 2015) - Kim, Keunyeong; Schmierbach, Michael G.; Bellur, Saraswathi (Saras); Chung, Mun-Young; Fraustino, Julia Daisy; Dardis, Frank; Ahern, Lee
Highlights: The data shows the distinct role of autonomy, control and attachment in creating enjoyment. Consistent with self-determination theory, feelings of autonomy and control contribute to enjoyment. Attachment to the customized avatar contributes to enjoyment through immersion. In general, players perceive a sense of control through customizing avatars. The feelings of autonomy and control are more critical predictors of enjoyment than attachment. Abstract: This study presents a model linking character customization and game enjoyment. Two separate studies using different types of customization (functional vs. aesthetic) were employed to test two competing mechanisms that explain the effects of customizing in-game characters: feelings of autonomy and control—rooted in self-determination theory—and perceived attachment to game characters. Additionally, this study investigated how these two divergent mechanisms influence game enjoyment through immersion-related experiences. The findings showed that the feelings of autonomy and control are consistently stronger explanations for enjoyment, regardless of customization type. The results suggest that similar to other entertainment media, games can appeal to individuals through the senses of autonomy, control, and attachment to a character; the first two prove more critical.